An acoustical and psychological study on contribution of lyrics in raga-based happy and sad Indian music. Issue 1 (April 2021) - Banerjee, A; Sanyal, S; Gayen, P; Roy, S; Patnaik, P; Ghosh, D
Abstract: A perfect complementary relationship between the lyric and the melody can give birth to a beautiful song. The melodic expression of a song is universal but the lyrical expression is not – lyric is culture specific because of its language dependence. Can melody itself communicate the core emotions of a song? Or does the addition of a lyrical sense significantly change its emotional experience? This study looks for the answers focusing on a unique subgenre of Indian Classical Music – Ragashroyi compositions, where the melodic movements sincerely follow the Raga pathways but the lyrics explore a much deeper and wider variety of emotions compared to Raga bandishes . Recordings were collected from two eminent vocalists (1 male, 1 female), each of whom was asked to sing (with proper lyrics) and hum (without meaningful lyrics) any two Bengali Ragashroyi compositions of two opposite emotions – happiness and sadness. Hurst Exponents, obtained from robust non-linear Detrended Fluctuation Analysis (DFA) of the recorded acoustic waveforms, were compared for each song-humming pair having same melodic structure to understand the acoustic contribution of the lyrics in a song quantitatively. A comparative audience response study was also conducted where several humming and song clips were played randomly and two groups (one which understands Bengali, the other which does not), each having 30 participants, were asked to mark the emotions and the characteristic features corresponding to each clip on 5 point Likert scale, and their responses were compared for each song-humming pair. This pilot study on Ragashroyi Indian music explores in depth the contribution of lyrics in vocal music from both the perspectives of computational acoustics and audience psychology.